2021
DOI: 10.1371/journal.pgen.1009339
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant binding of mutant HSP47 affects posttranslational modification of type I collagen and leads to osteogenesis imperfecta

Abstract: Heat shock protein 47 (HSP47), encoded by the SERPINH1 gene, is a molecular chaperone essential for correct folding of collagens. We report a homozygous p.(R222S) substitution in HSP47 in a child with severe osteogenesis imperfecta leading to early demise. p.R222 is a highly conserved residue located within the collagen interacting surface of HSP47. Binding assays show a significantly reduced affinity of HSP47-R222S for type I collagen. This altered interaction leads to posttranslational overmodification of ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Proper triple-helix formation as well as exit from the ER of procollagen molecules depends critically on HSP47, an ER-resident chaperone belonging to the serpin family. Ablation of HSP47 leads to early embryonic death in mice ( 6 ), and several missense mutations in humans and dogs give rise to Osteogenesis imperfecta ( 7 , 8 , 9 , 10 ). The exact mechanism by which HSP47 chaperones collagen folding and secretion is not entirely clear, yet.…”
mentioning
confidence: 99%
“…Proper triple-helix formation as well as exit from the ER of procollagen molecules depends critically on HSP47, an ER-resident chaperone belonging to the serpin family. Ablation of HSP47 leads to early embryonic death in mice ( 6 ), and several missense mutations in humans and dogs give rise to Osteogenesis imperfecta ( 7 , 8 , 9 , 10 ). The exact mechanism by which HSP47 chaperones collagen folding and secretion is not entirely clear, yet.…”
mentioning
confidence: 99%
“…Defects of the complex members affected this modification either by enhancing (defect in Hsp47 and Bip) or diminishing (defect in FKBP65) LH2 activity 34 . In contrast, Syx et al has stated that a mutant Hsp47, which showed a reduced binding to type I collagen, resulted in decreased LH2 44 . These inconsistent data suggest that Hsp47 may act as a positive or negative regulator of LH2 in a context-dependent manner.…”
Section: Discussionmentioning
confidence: 91%
“…Defects of the complex members affected this modi cation either by enhancing (defect in Hsp47 and Bip) or diminishing (defect in Fkbp65) LH2 activity 34 . In contrast, Syx et al has stated that a mutant Hsp47, which showed a reduced binding to type I collagen, resulted in decreased LH2 44 . These inconsistent data suggest that Hsp47 may act as a positive or negative regulator of LH2 in a context-dependent manner.…”
Section: Discussionmentioning
confidence: 91%